Police perceptions of residents in a high-crime area in Trinidad and Tobago: Community framing and crime wars - Watson, Danielle (Criminology & criminal justice, 2021)
This article examines police perceptions of residents of a marginalized community in Trinidad and Tobago. The discourses of 40 members of the Trinidad and Tobago Police Service are examined to determine how they define residents of the community and situate them within specific interactive contexts. Results show that the officers typically have extremely negative views of the community and its residents, which amplify their perceptions of policing as difficult and dangerous. The potential impact of these perceptions upon police practices, officer well-being and police–community relations are discussed. The study contributes to the emerging scholarly dialogue on policing in the global South and highlights the benefits of discourse analysis within country case studies to elucidate country-specific nuances in police–community relations.